Electricity access, human development index, governance and income inequality in Sub-Saharan Africa - Samuel Asumadu Sarkodie; Samuel Adams (Energy Reports, 2020)
Consistent with the Sustainable Development Goal 7 of ensuring access to clean and modern energy technologies, this study examined the nexus between access to electricity, human development index, political system environment, income level, and income inequality. We employed a nonparametric regression technique with Driscoll-Kraay standard errors from 1990 to 2017 in Sub-Saharan Africa. The study revealed that income inequality has a negative effect on access to electricity whereas income level and human development have a positive impact on access to electricity. Enhancing the political system environment in Sub-Saharan Africa is crucial to ensuring access to clean and modern electricity. The negative effect of political system on income inequality means that good governance environment reduces income inequality. Income inequality is found to reduce human development, as such, social protection policies that reduce poverty are essential to minimize the vulnerability to poverty. The study highlights that the effective promotion of labor markets and the improvement of socio-economic capacity to manage unemployment, infirmity, and disability will decrease income inequality, hence, promote human development.
Keywords: 330; Sustainable development; Access to electricity; Driscoll-Kraay; Human development index; Income inequality; Sub-Saharan Africa